How to set up PayPal instant payment notification - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2013)
"Every e-commerce website needs a payment processing system, and PayPal is the most widely used processing system in the world. If you're a web developer, being able to implement a PayPal Instant Notification System is a must have skill for your toolbox. What Is PayPal IPN? PayPal IPN is used for managing orders and creating transaction reports. Instant Payment Notification is a message service that automatically notifies merchants of events related to PayPal transactions. Merchants can use it to automate back-office and administrative functions, like fulfilling orders and providing customers with order status."--Resource description page.
Title from resource description page (viewed April 2, 2015).
Keywords: PayPal (Firm); Electronic funds transfers; Electronic books